The Impact of Tourism Development on the Socio-Economic Conditions of the Jikumerasa Village Community, Buru Regency - M. Rusdi, M. Rusdi; Sangaji, Radi Udin Alfian; Ismail, Ismail; Muhammad Yahya,; Rosmawati Taherong, (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Tourism development, when unplanned, it can exert a range of socio-economic impacts, primarily stemming from the divergence in cultural perspectives between tourists and local residents. This research delves into the consequences of tourism development on the socio-economic fabric of the Baikolet beach community and strives to identify the key drivers behind these impacts. This research emplyed descriptive qualitative method, it employed purposive sampling to select informants, and gathered data through a combination of observation, interviews, and documentation. Data analysis encompassed data reduction, presentation, verification, and the formulation of data-driven conclusions. This research reveals that tourism development carries both positive and negative repercussions for the community. On the positive side, it contributes to increased public awareness, fosters social interaction, generates employment opportunities, and augments community income. However, there are also negative outcomes, such as social transformations that influence and erode local culture, as well as environmental pollution. These impacts are attributed to several factors, including the community's aspiration to enhance their economic well-being, the resultant social and cultural shifts, and the level of awareness among both tourists and local residents.